Application of Remote Sensing and GIS in Monitoring Land Use and Land Cover Change in the Nandoni Dam Basin - Lilimu, Maanda Danson (School of Architecture, Planning and Geomatics, 2024)
Land use activities and land cover (LULC) changes have been widely acknowledged as the main drivers of environmental change at all spatial-temporal scales in some South African dam basins. The consequence of these land use activities causes encroachments, land cover changes, sediment deposits, deforestation, and severe flood damages, which reduces water storage capacity and economic tourism activities in dam basins. The challenges of land use activities have highlighted the need to monitor LULC changes in the Nandoni Dam basin. Remote sensing and Geographical Information Systems (GIS) methods offer the possibility of monitoring LULC changes, which could help dam basin management agencies make spatio-temporal decisions to preserve water storage capacity in dam basins. This study investigated the Nandoni Dam basin's LULC changes using Landsat TM 1997, 2005, and ETM+ 2021 images. The six LULC classes classified are water bodies, forests, floodplains, built-up land, bare land, and agricultural land. The images were successfully delineated using GIS zoning boundary data and then classified through a supervised maximum likelihood classifier. The results of the classified images showed significant changes in all classes, with built-up land being the major encroachment into the dam basin, covering 18.28% in 1997, 21.46% in 2005, and 19.12% in 2021. These findings provide considerable spatio-temporal information on factors causing LULC change patterns and improve the understanding of the amount and rate of encroachment of the dam basin. The results are recommended to the landowners, water authorities and the government for monitoring LULC change patterns in the Nandoni Dam basin. Keywords: remote sensing, GIS, land use, land cover, Nandoni Dam basin